Research on Temporal Structures and Cultural Memory Mechanisms in Digital Exhibition Design of Intangible Cultural Heritage - Dong, Hao (Journal of Social Science and Humanities, 2025)
With the rapid penetration of digital technologies into the field of cultural presentation, the modes of representation and pathways of understanding for intangible cultural heritage (ICH) are undergoing profound transformation. Among these changes, temporal structure, as a core element embedded in ICH practices, is being reorganized and reinterpreted within digital exhibition environments. Taking “temporality” as its analytical point of departure, this study examines how digital media reshape the indigenous rhythms of ICH through mechanisms of compression, reconstruction, and participation, and further analyzes how such temporal restructuring influences the formation of cultural memory. The study proposes a three-layer temporal structure model—authentic time, representational time, and experiential time—and summarizes the temporal translation methods found in various media forms, including video, immersive environments, interactive systems, and algorithm-driven platforms. Based on this model, the paper identifies four cultural memory mechanisms in digital ICH exhibition: visualization, contextualization, enactment, and communalization. The findings suggest that digitization does not simply reproduce traditional temporalities; rather, it generates composite temporal structures shaped through design mediation, media logic, and participant behavior, thereby influencing how cultural memory is generated and disseminated. This analysis provides theoretical grounding and methodological insight for temporal design and memory construction in the digital display of intangible cultural heritage.